Measurement of corticosterone in mice: a protocol for a mapping review. (February 2020) - Leenaars, Cathalijn H.C.; van der Mierden, Stevie; Durst, Mattea; Goerlich-Jansson, Vivian C; Ripoli, Florenza Lüder; Keubler, Lydia M; Talbot, Steven R; Boyle, Erin; Habedank, Anne; Jirkof, Paulin; Lewejohann, Lars; Gass, Peter; et al.
Severity assessment for experiments conducted with laboratory animals is still based mainly on subjective evaluations; evidence-based methods are scarce. Objective measures, amongst which determination of the concentrations of stress hormones, can be used to aid severity assessment. Short-term increases in glucocorticoid concentrations generally reflect healthy responses to stressors, but prolonged increases may indicate impaired welfare. As mice are the most commonly used laboratory animal species, we performed a systematic mapping review of corticosterone measurements in Mus musculus, to provide a full overview of specimen types (e.g. blood, urine, hair, saliva, and milk) and analysis techniques. In this publication, we share our protocol and search strategy, and our rationale for performing this systematic analysis to advance severity assessment. So far, we have screened 13, 520 references, and included 5337 on primary studies with measurements of endogenous corticosterone in M. musculus . Data extraction is currently in progress. When finished, this mapping review will be a valuable resource for scientists interested in corticosterone measurements to aid severity assessment. We plan to present the data in a publication and a searchable database, which will allow for even easier retrieval of the relevant literature. These resources will aid implementation of objective measures into severity assessment.